2004
DOI: 10.1590/s1678-77572004000300006
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the presence of apical deviation with employment of automated handpieces with continuous and alternate motion for root canal preparation

Abstract: he present study conducted an in vitro evaluation of the presence of apical deviation on the root canal preparation of the mesiobuccal roots of human maxillary molars employing automated handpieces with continuous motion, the Pow R system (Moyco Union Broach), and alternate motion, the M4 system (Kerr). Analysis of the presence of apical deviation was carried out by means of radiographs obtained on a radiographic desk fabricated for the study. The results demonstrated the lack of statistically significant diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…From the obtained results, there was significant interaction between the curve location and the degree of canal curvature, which means, independently on the instrument size (F3, F4 or F5), in point A, canals of 20° presented wear mean smaller than canals of 40°, but in point B this difference was not significant ( Table 2 ). Such fact has been demonstrated in a previous 12 study, where M4 System was used: canals with larger curvature degree showed greater apical wear.…”
Section: Discussionsupporting
confidence: 69%
“…From the obtained results, there was significant interaction between the curve location and the degree of canal curvature, which means, independently on the instrument size (F3, F4 or F5), in point A, canals of 20° presented wear mean smaller than canals of 40°, but in point B this difference was not significant ( Table 2 ). Such fact has been demonstrated in a previous 12 study, where M4 System was used: canals with larger curvature degree showed greater apical wear.…”
Section: Discussionsupporting
confidence: 69%
“…The oscillatory and rotary systems were powered by an electric engine because compressed air-driven systems do not allow torque control and may undergo air pressure variations that might affect the rotational speed and torque (10).…”
Section: Discussionmentioning
confidence: 99%
“…The crowns were maintained to simulate, as closely as possible, the clinical endodontic practice, in which the interference of cervical dentin projections creates tensions on the files during root canal instrumentation (15). The oscillatory and rotary systems were powered by an electric engine because compressed air-driven systems do not allow torque control and might undergo air pressure variations that might affect the rotational speed and torque (16,17). Measurements were performed in duplicate to check the intra-examiner agreement.…”
Section: Discussionmentioning
confidence: 99%